Pembinaan Prestasi Perguruan Pencak Silat Persaudaraan Setia Hati Terate Ranting Kedungadem Kabupaten Bojonegoro - Jaya Catur Arya Utama; Noortje Anita Kumaat (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to understand and describe the development of achievements in the Pencak Silat institution of Setia Hati Terate Branch Kedungadem, Bojonegoro Regency. The phenomenon of Pencak Silat PSHT has significantly contributed to elevating Indonesia's name in both national and international martial arts. However, to maintain competitiveness with other countries, efforts are needed to universally develop achievement development. Challenges faced in advancing the achievement development of Pencak Silat PSHT in the Kedungadem branch of Bojonegoro Regency include insufficient funding, underutilization of existing facilities, and a lack of specialized training for athletes and coaches. This research adopts a qualitative approach, intentionally selecting the location as the PSHT Training Center in the Kedungadem Branch of Bojonegoro Regency. The results indicate that achievement development in the Kedungadem branch meets standards for coaches, demonstrating professionalism and competence. The sports branch of Pencak Silat PSHT in the Kedungadem branch has a considerable number of potential athletes. The training program is structured and continuous, with sufficient budgetary allocations to fund athlete training and participation in competitions. The applied training program is well-organized, with training sessions held three times a week. The Pencak Silat PSHT branch in Kedungadem possesses equipment, including mats (10m x 10m), two sandbags, five wooden dummies, and three pairs of body protectors.